Synergistic neurotrophic effects of piracetam and thiotriazoline - O. A. Gromova; I. Yu. Torshin; A. V. Pronin; A. Yu. Volkov (Неврология, нейропсихиатрия, психосоматика, 2016)
The paper considers the synergy between the nootropic drug piracetam and the metabolic agent thiotriazoline that maintains energy metabolism and survival of neurons and other types of cells. Piracetam, a nootropic drug, a chemical pyrrolidone derivative, is used in neurological, psychiatric, and narcological practice. There is evidence on the positive effect of piracetam in elderly and senile patients with coronary heart disease. This drug is supposed to stimulate redox processes, to enhance glucose utilization, and to improve regional blood flow in the ischemic brain regions. Due to its action, the drug activates glycolytic processes and elevates ATP concentrations in brain tissue. Thiotriazoline is a compound that has antioxidant, anti-ischemic properties. The co-administration of piracetam and thiothriazoline is an innovation area in the treatment of stroke and other brain damages, especially in insulin resistance and high blood glucose levels. The paper considers the neurobiological properties of thiotriazoline and piracetam, which synergistically exert neuroprotective and neurotrophic effects.